Socio-environmental survey of a forest hamlet proximate to Neora Valley National Park in the Eastern Himalayas, India - Sayan Bhattacharya; Sudipta De; Arkajyoti Shome; Abhishek Dutta (Research Centre of Inorganic Materials and Complexs, 2019)
The Eastern Himalayas have significant impact on the climate and biodiversity of the Indian Subcontinent. The Himalayan region has shown consistent warming trends in recent times, which can significantly affect the biodiversity, agriculture and local livelihoods. Many scattered hamlets are found in this zone and some of them are proximate to the forests enriched with endemic biodiversity. Icchey Gaon (27.1336oN, 88.5657oE; Altitude 5,600 feet) is a small village situated in Kalimpong district, India in the Eastern Himalayas. Icchey Gaon is situated proximate to Neora Valley National Park, which is located in the Eastern Himalayas as a global ‘biodiversity hotspot’. The village is one of the newest tourist destinations in the Eastern Himalayas. The village area is also a centre of Cinchona plantation since 19th century. The adjacent areas of Icchey Gaon have extensive coverage of Cinchona plantation. The survey work was done in April, 2017 by visiting Icchey Gaon village in Kalimpong, West Bengal. The study focuses on an interdisciplinary understanding of the physical and cultural environment of the forest and mountain areas. The survey work integrates the perspectives of human and social ecology, ecosystem services and sustainable development. Primary data were gathered through field survey and direct contact with common people and authorized centres of the region. Structured questionnaires and semi-structured interviews supplemented by field notes were arranged to collect data from the village areas in Icchey Gaon. The length of each interview was about 40–50 minutes and was supplemented by field notes. Focuses were given on demography, agriculture, livestock management, traditional water management, education, culture, health, waste management, disaster management, biodiversity, joint forest management, ecosystem services and human animal conflict. Biodiversity of the region was documented by visiting the forest areas and the nature interpretation centre situated in Neora Valley National Park. There is an urgent need for implementing an integrated sustainable development system for the conservation of forest ecosystems and traditional human settlements in and around Neora Valley forest. Management strategies have been suggested for conserving the forest biodiversity and socio-economic condition of the hamlet. Bringing local communities into protected area management can have significant positive impact on long-term biodiversity conservation in the transboundary Himalayan landscapes. Extensive study is necessary in the Eastern Himalayas to explore the socio-ecological conditions in the context of climate change.